ChemInform Abstract: Copper‐Catalyzed Formation of α‐Alkoxycycloalkenones from N‐Tosylhydrazones. Issue 12 (March 2016) - Su, Naijing; Theorell, Juliana A.; Wink, Donald J.; Driver, Tom G.
Abstract: Readily available N‐tosylhydrazones bearing an ortho alkene part with pendant ester substituent are subjected to conditions A).